Pengendali Kecepatan Robot Beroda dengan Proporsional Integral Derivative dan Tuning Ziegler-Nichols - Bagus Sawung Timur; Eko Setiawan; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Wheeled robot is a technological innovation that facilitates exploration mobilization. The use of wheeled robots in exploring unstable fields is often a quite troublesome obstacle. Based on these problems, in this study, the design of a control system on wheeled robots was carried out that can regulate the speed of the robot both in the incline and the derivative field. The speed monitoring process on the robot uses an optocoupler sensor which is then controlled using Arduino UNO. For the method used as a determinant and speed control regulator, this research uses the PID (Proportional Integral Derivative) method with the Ziggler-Nichols tuning method to the field conditions being faced. In this study, testing is based on several scenarios. In testing the upper limit and lower limit of 225-255 PWM experiments found errors of 60o and 90o. Based on testing to find the PID parameters found results Kp 2.4, Ki 1.92, Kd 0.75. From the results of PID testing on the system obtained an average settling time of 3.6 seconds